POTENSI JAMUR ENTOMOPATOGEN Metarhizium anisopliae, Beauveria bassiana dan Streptomyces sp. TERHADAP MORTALITAS Lepidiota stigma PADA TANAMAN TEBU - Aditya R. Hidayah; Wiwik Sri Harijani; Wiludjeng Widajati; Dina Ernawati (UPN VETERAN JAWA TIMUR, 2019)
Sugarcane is a plant which only grow in tropical. Plant pests and plant diseases in cultivation have never been separated. One of the important pests of sugarcane is uret root destroyers (Lepidiota stigma). The pests can reduce crop yields by 50%. One of the best alternatives for uret pest control which can be safety and environmentally friendly by using biological agents. The biological agents for pests control has a good potential and prospects because they are host-specific and harmless to human. This study was conducted to determine the effectiveness of Metarhizium anisopliae, Beauveria bassiana and Streptomyces sp.mortality Lepidiota stigma. This study used 3 treatments in a completely randomized design (CRD) with each repeated 9 times. The results showed that for four observations at intervals of seven days of observation. The ability of three biological agents has different varieties in turning off the test insect, this is indicated by the highest mortality percentage of M. anisopliae with total mortality of 88.89%.